2014
DOI: 10.1371/journal.pone.0105070
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Fisetin on Cisplatin-Induced Nephrotoxicity in Rats via Modulation of NF-κB Activation and Antioxidant Defence

Abstract: Nephrotoxicity is a dose-dependent side effect of cisplatin limiting its clinical usage in the field of cancer chemotherapy. Fisetin is a bioactive flavonoid with recognized antioxidant and anti-inflammatory properties. In the present study, we investigated the potential renoprotective effect and underlying mechanism of fisetin using rat model of cisplatin-induced nephrotoxicity. The elevation in serum biomarkers of renal damage (blood urea nitrogen and creatinine); degree of histopathological alterations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 44 publications
9
106
1
Order By: Relevance
“…It has shown synergistic activities with other anticancer agents (i.e. cisplatin and cyclophosphamide) in different carcinoma cell lines [2,3] and acts as an adjunct in cancer therapy to alleviate specific adverse effects related to cytotoxic agents or other therapeutics, including protection against ovariectomy-induced bone loss in mice [4] and has a renoprotective effect in cisplatininduced nephrotoxicity in rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown synergistic activities with other anticancer agents (i.e. cisplatin and cyclophosphamide) in different carcinoma cell lines [2,3] and acts as an adjunct in cancer therapy to alleviate specific adverse effects related to cytotoxic agents or other therapeutics, including protection against ovariectomy-induced bone loss in mice [4] and has a renoprotective effect in cisplatininduced nephrotoxicity in rats [5].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism of anthracycline-induced organ damage includes the generation of reactive oxygen species, inflammation, caspase activation and apoptosis (Sahu et al, 2014(Sahu et al, , 2015. Our previous research has suggested that the activation of the nuclear factor-κB (NF-κB) pathway is involved in the development and progression of epirubicin-induced hepatotoxicity and reactive oxygen species play a crucial role in aggravating inflammation by activating the NF-κB pathway (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, fisetin inhibits LPS)-induced pro-inflammatory cytokine release and also activation of macrophages (Kim et al, 2012;Liu et al, 2010). Fisetin also showed its antidepressant properties (Sahu et al, 2014).…”
Section: Discussionmentioning
confidence: 97%